11 Iris Cerclage: 360 Degree Running Pupil Margin Suture (Video Atlas of Anterior Segment Repair and Reconstruction, 2019)
A pupillary cerclage procedure is an elegant and effective method to wind a 10-0 polypropylene suture around a dysfunctional, mydriatic pupil margin, effectuating a more physiologic aperture to reduce undesired photic symptoms and restore a more normal body image.
Keywords: Mydriasis; pupil; cerclage; iris